KOMPARASI PENGARUH RELATIONSHIP MARKETING DENGAN PENGARUH MEDIASI KEPUASAN DALAM MEMBANGUN LOYALITAS PASIEN RUMAH SAKIT ISLAM DI KABUPATEN BANYUWANGI - Mohamad Dimyati (INFERENSI: Jurnal Penelitian Sosial Keagamaan, 2016)
This study are aimed to examine the effect of Relationship marketing to patient satisfaction, relationship marketing to the loyalty of the patient, patient satisfaction to loyalty patient, and to compare the influence of relationship marketing with mediating influence of patient satisfaction in creating patient loyalty on Banyuwangi Islamic Hospital. The research instrument to collect the data is using a questionnaire. The population is outpatient and inpatient of Banywangi Islamic hospital (RSI) (Fatimah, Al-Huda, Nahdatul Ulama). The research sample is determined by multistage sampling method. The numbers of samples are 120 respondents. The method of analysis is using Structural Equation Modeling (SEM). The result shows that relationship marketing has a significant positive effect on patient satisfaction, relationship marketing has a significant positive effect on patient loyalty, satisfaction of patients has a significant positive effect on patient loyalty and also relationship marketing has a greater influence than the influence of mediation satisfaction in influencing the creation of loyalty to Banyuwangi Islamic Hospital patients.